Bacillus subtilis DSM29784 attenuates Clostridium perfringens-induced intestinal damage of broilers by modulating intestinal microbiota and the metabolome - Wang, Yuanyuan; Xu, Yibin; Cao, Guangtian; Zhou, Xihong; Wang, Qian; Fu, Aikun; Zhan, Xiuan (Frontiers in Microbiology, 2023)
Necrotic enteritis (NE), especially subclinical NE (SNE), without clinical symptoms, in chicks has become one of the most threatening problems to the poultry industry. Therefore, increasing attention has been focused on the research and application of effective probiotic strains as an alternative to antibiotics to prevent SNE in broilers. This study determined the effect of Bacillus subtilis (BS) on the prevention of SNE induced by Clostridium perfringens (CP) in broilers, while also demonstrating the associated modulation of intestinal health, and clarifying the underlying microbiota-dependent mechanism. Gene transcription was assessed using quantitative real-time PCR. The microflora and metabolite composition were analyzed by 16S rDNA sequencing and gas chromatograph–mass spectrometry. The negative (Ctr) and positive (SNE) broiler groups were fed a basal diet, whereas the two treatment groups received basal diets supplemented with BS (1 × 109 cfu /kg) or 10 mg/kg enramycin (ER), respectively. The SNE and treatment groups were then infected with CP. BS, similar to ER, effectively attenuated CP-induced poor growth performance. Moreover, BS pretreatment increased villi height, claudin-1 expression, maltase activity, and immunoglobulin abundance, while decreasing lesional scores, as well as mucosal IFN-γ and TNF-α concentrations. In addition, BS pretreatment increased the relative abundance of beneficial bacteria and decreased that of pathogenic species; many lipid metabolites were enriched in the cecum of treated chickens. These results suggest that BS potentially provides active ingredients that may serve as an antibiotic substitute, effectively preventing SNE-induced growth decline by enhancing intestinal health in broilers.